2017
DOI: 10.21037/jtd.2017.07.56
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone marrow-derived endothelial progenitor cells and angiogenic responses in chronic obstructive pulmonary disease

Abstract: Increased vascularity of the bronchial sub-mucosa is a cardinal feature of chronic obstructive pulmonary disease (COPD) and is associated with disease severity. Capillary engorgement, leakage, and vasodilatation can directly increase airway wall thickness resulting in airway luminal narrowing and facilitate inflammatory cell trafficking, thereby contributing to irreversible airflow obstruction, a characteristic of COPD. Airway wall neovascularisation, seen as increases in both the size and number of bronchial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…However, the EPS population is not homogeneous. EPC is defined as CD34 + VEGFR2 + CD45 dim [ 36 ]. Other authors use coexpression of CD34 and fibroblast growth factor receptor 1 to identify EPC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the EPS population is not homogeneous. EPC is defined as CD34 + VEGFR2 + CD45 dim [ 36 ]. Other authors use coexpression of CD34 and fibroblast growth factor receptor 1 to identify EPC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work also showed that EPCs treated with CSE in vitro displayed decreased capacities of proliferation, adhesion, and secretion 29 . Moreover, extensive data have established that circulating EPCs are decreased in COPD subjects 30 , but the enumeration of EPCs homing into the lungs of COPD patients has not been studied. In this study, we explored the EPCs homing into the lung and investigated the protective effect of PU.1 for the first time in CSE-induced emphysematous mice.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of BM-EPC in bone milieu contributes to bone marrow angiogenesis [2,14]. In regenerative medicine, BM-derived EPCs could potentially be used as therapeutic strategies to combat several diseases, including wound healing, myocardial infarction, and chronic obstructive pulmonary disease [1518]. Both hypercholesteremia and HHcy are accepted as common risk factors for the development of vascular disease, thus limiting EPC-mediated vascular repair [19,20].…”
Section: Discussionmentioning
confidence: 99%